Effect of Anti-Transpirants foliar application on productivity and quality of Egyptian cotton under water stress conditions in clay soils - ELashmouny, Amany Ahmed; Moursi, ElSayyed AbuAl-Futouh (Journal of agricultural, environmental and veterinary sciences, 2024)
Two field experiments were conducted at Sakha, Agricultural Research Station, Egypt in two growing seasons during 2021 and 2022 seasons, to study the effect of three irrigation intervals (every 15, 30 and 45 days) and four foliar application with some anti-transpirants (without , linseed Oil (7%), Pure Gylatine (1.5 %) Magnesium Carbonate for dusting (250 g / plot), Potassium Silicate (3cm3 K2SiO3 / liter) on the growth, productivity, quality of Egyptian cotton plants (Super Giza 94 cultivar) and some water relations .The experiment was designed by using split plot design with three replicates. The results showed that, irrigation cotton plants every 30 days significantly increased leaf water content%, chlorophyll (a) in the second season, chlorophyll (b), number of open bolls / plant, earliness % in the second season, seed cotton yield, boll weight, seed index all in the two growing seasons compared with other two irrigation intervals. On the other hand, irrigation every 15 days was more effective on plant height, number of fruiting branches per plant in both seasons, fineness in the first season, fiber length in the second season and fiber strength in the two seasons. Foliar application of anti- transpirants significantly increased in the most studied characters, leaf water content%, chlorophyll a and b , plant height, number of fruiting branches, number of open bolls, earliness %, seed cotton yield, boll weight , seed index , fiber fineness , fiber strength and fiber length except fiber uniformity which was not affected in the two seasons as compared with the control in the two seasons. The highest values were obtained from potassium silicate compared with other anti- traspirants. Concerning the interaction effect between irrigation interval and anti-transpirants , the data indicated that the application of Potassium Silicate and irrigation cotton plants every 30 days produced the highest significant increase in leaf water content %, chlorophyll a , chlorophyll b , number of fruiting branches ,seed cotton yield and earliness % in the first and second season.